Translation Methods for Food Culture-specific Expressions in David Hawkes’ English Translation of the Chu ci - Shi, Qingling; Tian, Chuanmao (Classical Literature, 2024)
The Chu ci, a significant legacy of ancient Chinese culture, showcases a diverse range of culinary vocabulary that mirrors the lifestyle of the ancient Chu people and reflects the deep-rooted Jingchu culture of China. This paper focuses on analyzing the translation methods of food-related vocabulary in the Chu ci, with a specific focus on the pieces known as the “Da zhao” (“The Great Summons”）and “Zhao hun” (“Summons of the Soul”) in the canon, which serve as the primary research object in this study. The present study primarily investigates the influential translation of the Chu ci by the renowned sinologist David Hawkes, namely, The Songs of the South (1985). It aims to explores the methods employed by Hawkes in translating the food culture-specific expressions in the Chu ci. The research findings were that as a distinguished sinologist, Hawkes took into consideration the cultural background and cognitive habits of the target readers in translating. He utilized various translation methods such as interpretation, adaptation and communicative translation to effectively interpret the original text. Besides, the paper evaluates the shortcomings present in Hawkes’ translation, including mistranslations and omissions. The goals of this study is to offer some insights and guidance for future translators, promote cross-cultural dissemination and understanding of Chinese culinary culture, and enhance global recognition and appreciation of the unique charm of Chinese civilization.